Oracles : - Thompson, Donald N. (Harvard Business Review Press, 2012)
By showing successes and failures of real organizations, and identifying the common roadblocks they’ve overcome, Oracles offers a guide to begin testing expertise against the collective wisdom of employees and the market—all to the benefit of their bottom line.